Concept of the «Тrem» and «Тerminology» of modern chinese language. - Altayeva, M. T. (Journal of Oriental Studies, 2016)
In the article are studied concept of the «term» and «terminology» of chinese language on the example of diplomatic terminology. Keywords: .